Progress in the use of antisense oligonucleotides for vaccine improvement - Batista-Duharte, Alexander [UNESP]; Sendra, Luis; Herrero, Maria José; Téllez-Martínez, Damiana [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Aliño, Salvador Francisco (MDPI, 2020)
Antisense oligonucleotides (ASOs) are synthetically prepared short single-stranded deoxynucleotide sequences that have been validated as therapeutic agents and as a valuable tool in molecular driving biology. ASOs can block the expression of specific target genes via complementary hybridization to mRNA. Due to their high specificity and well-known mechanism of action, there has been a growing interest in using them for improving vaccine efficacy. Several studies have shown that ASOs can improve the efficacy of vaccines either by inducing antigen modification such as enhanced expression of immunogenic molecules or by targeting certain components of the host immune system to achieve the desired immune response. However, despite their extended use, some problems such as insufficient stability and low cellular delivery have not been sufficiently resolved to achieve effective and safe ASO-based vaccines. In this review, we analyze the molecular bases and the research that has been conducted to demonstrate the potential use of ASOs in vaccines.
Keywords: Adjuvants; Antisense oligonucleotide; Cancer; Infectious disease; Vaccines